2001
DOI: 10.1117/1.1344189
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of hypermethylated triplet repeats in vitro by cationic nanoparticles

Abstract: Genomic DNA contains many higher-order structural deviations from the Watson-Crick global average. The massive expansion and hypermethylation of the duplex triplet repeat (CCG)(n)(CGG)(n) has characteristic higher-order structures that are associated with the fragile X syndrome. We have used luminescent mineral nanoparticles of protein-sized cadmium sulfide in optical assays to detect anomalous DNA structures. The photoluminescence of these particles is sensitive to the presence and nature of adsorbates. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…From these experiments, valuable biophysical insight has been gained into the way that different DNAs bind to generic protein-sized curved surfaces without the need for researchers to label the DNA or use radioactivity (43)(44)(45)(46). Some of these unusual DNA structures are correlated with human disease (47), and thus the development of this optical detection scheme is of interest to the bioanalytical community.…”
Section: Quantum Dots As Fluorescent Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…From these experiments, valuable biophysical insight has been gained into the way that different DNAs bind to generic protein-sized curved surfaces without the need for researchers to label the DNA or use radioactivity (43)(44)(45)(46). Some of these unusual DNA structures are correlated with human disease (47), and thus the development of this optical detection scheme is of interest to the bioanalytical community.…”
Section: Quantum Dots As Fluorescent Probesmentioning
confidence: 99%
“…In these experiments, the quantum dots are not particularly well passivated, but their surfaces are modified with cationic or hydrogenbonding groups that are presumably attractive to the anionic DNA polymer. Photoluminescence titrations are then performed with short DNA oligomers that are either "normal" or "unusual" in terms of local structure and flexibility (43)(44)(45)(46). The shape of the emission spectrum does not change, only its intensity.…”
Section: Quantum Dots As Fluorescent Probesmentioning
confidence: 99%
“…The use of the photoluminescence of quantum dots for detection of different DNA sequences, based on the differential adsorption of DNAs to the quantum dot surface due to local D N A structural d efo rm ation , h as been rep orted by the M u rphy group. [101][102][103][104][105][106] Local structural and dynamic distortions within DNA are correlated with some genetic diseases, and thus, quantum dots, unique probes with curvature on the size scale of the distortion, may be wellsuited as optical detectors of DNA deformation and damage.…”
mentioning
confidence: 99%
“…We have shown that quenching of CdS luminescence is an indirect approach to detecting DNA structure and is dependent on nanoparticle surface charge and functionality. 1,2,13 However, the luminescence signal does not provide direct molecular information. A technique, which provides chemical information about adsorbates at nanosize metallic surfaces, is surface-enhanced Raman scattering (SERS) spectroscopy.…”
Section: Introductionmentioning
confidence: 98%